Evaluating ERP Information Security Using ISO/IEC 27001:2013 Standard in Agricultural Technology Enterprises - Hastuti, Puji; Dewi Cantika, Nourma Islam; Pratama, Aditya; Saputra, Dhanar Intan Surya (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2025)
Data security is an essential component of ERP system management, particularly given the increasing cyber dangers in the digital age.  This study assesses the maturity of ERP-based information security at PT BroilerX Yogyakarta using the ISO/IEC 27001:2013 standard.  The growing dependence on digital platforms in agriculture has expedited the implementation of ERP solutions, like Odoo, to optimize business processes.  This research employs a qualitative descriptive case study methodology to examine the implementation of ten ISO domains, utilizing data gathered from interviews with the IT team and analyzed through the Capability Maturity Model Integration.  The findings indicate that the majority of domains attained a maturity level of 4 (Managed), signifying consistent and thoroughly documented processes, although Human Resource Security and Incident Management remained at level 3 (Defined), highlighting the necessity for enhanced automation and proactive incident management.  These findings underscore both the strengths and flaws in ERP security implementation and offer actionable advice to enhance the Information Security Management System (ISMS).  This research contextualizes ISO/IEC 27001:2013 within a poultry agritech enterprise, thereby enhancing understanding of the integration of international security standards in technology-driven agribusiness and providing practical insights for similar organizations aiming to bolster their resilience against cyber threats.